Ionic strength modulates size-controlled ecotoxicity of citrate-coated silver nanoparticles to Daphnia magna in complex environmental matrices - Ping Luo; Zhenghao Xu; Jiageng Zhang; Xin Wang; Xiujun Gu; Lizhang Wang; Dejun Yang; Jiachao Jiang (Environmental Geochemistry and Health, 2025)

SNMPs Function as Molecular Bridges between OBPs and ORs in the Olfactory Recognition of Clostera Retitura (Walker) (Lepidoptera: Notodontidae) - Tianzi Gu; Xinwen Chen; Tianyu Ma; Jia Ye; Dejun Hao; Longwa Zhang (Journal of Chemical Ecology, 2025)

Dynamic motion response of a large-scale steel aquaculture cage during towing - Shuai Niu; Zhi Wang; Lianyi Guo; Lianghao Tang; Tianyu Gu; Can Cui; Dejun Feng; Fukun Gui; Xu Yang (Frontiers in Marine Science, 2025)
As global aquaculture ventures further into offshore environments, the safe transport of large-scale aquaculture net cages across varied marine conditions has become a critical technical concern. This study conducts a detailed numerical simulation of the wet towing process for an octagonal aquaculture cage using AQWA software, systematically examining the effects of towline length, towing speed, towing configuration, and environmental factors on the cage’s dynamic response and towline load characteristics. The findings reveal that towline length and towing speed are pivotal in determining the pitch amplitude of the cage and the resulting towline tension. Compared to a towline length of 200 m, using a towline length of 150 m combined with a towing speed of 0.5 m/s reduces pitch amplitude by 51.6% and towline tension by 24.8%. Additionally, an interval towing arrangement significantly enhances cage stability while minimizing towline stress. Under conditions of low wave height and longer wave period, the cage’s motion response remains stable, contributing to enhanced transport safety. This research offers critical theoretical foundations and optimization strategies for the wet towing design considerations of offshore aquaculture cages, providing valuable insights to advance transport safety in challenging marine environments.

Achieving the enrichment of denitrification phosphorus removal bacteria to promote endogenous denitrifying phosphorus removal in the micro-pressure swirl reactor for different carbon-to-phosphate ratio wastewater treatment - Wenai Liu; Xin Liang; Xingyu Zhu; Chen Dai; Tong Zhang; Qi Liu; Jingying Gu; Dejun Bian (Journal of Water Process Engineering, 2025)

Evaluating the Seasonal Cycle of the South China Sea Monsoon in CMIP6 Models - Bin Zheng; Jingxuan Qu; Yanyan Huang; Dongdong Peng; Dejun Gu; Chunhui Li; Ruping Huang (Journal of Meteorological Research, 2025)

Mechanisms of persistent heavy rainfall related to 10–30‑day oscillation during pre- and post-monsoon-onset periods in the first rainy season over South China - Chunhui Li; Jing Wang; Dejun Gu; Ailan Lin; Bin Zheng; Dongdong Peng; Jinhai He (Climate Dynamics, 2024)

Afforestation enhances glomalin-related soil protein content but decreases its contribution to soil organic carbon in a subtropical karst area - Rui Gu; Kongcao Xiao; Zihong Zhu; Xunyang He; Dejun Li (Journal of Environmental Management, 2024)

New easily recycled carrier based polyurethane foam by loading Al-MOF and biochar for selective removal of fluoride ion from aqueous solutions - Zhe Wang; Xinyue Gu; Xinbo Zhang; Xiao Wang; Jianqing Zhang; Ying Liu; Xinai Tan; Ying Zhao; Dejun Kang; Wenshan Guo; Huu Hao Ngo (Science of The Total Environment, 2023)

High plant species diversity enhances lignin accumulation in a subtropical forest of southwest China - Zongyao Qian; Rui Gu; Kun Gao; Dejun Li (Science of The Total Environment, 2023)

Phase determination of persistent heavy rainfall related to 10–30-day intraseasonal oscillation over Southeastern China - Bin Zheng; Dejun Gu; Ailan Lin; Dongdong Peng; Chunhui Li; Yanyan Huang (Theoretical and Applied Climatology, 2022)

Record-breaking heat wave in southern China and delayed onset of South China Sea summer monsoon driven by the Pacific subtropical high - Kaiqiang Deng; Song Yang; Dejun Gu; Ailan Lin; Chunhui Li (Climate Dynamics, 2020)
We investigate a record-breaking heat wave in southern China (SC) and explore its association with the South China Sea (SCS) summer monsoon (SCSSM), using station observations and various reanalysis products. This heat wave event started in mid-May 2018 and persisted more than 15 days, when the maximum air temperature anomaly exceeded 6 °C. Meanwhile, the onset of the SCSSM was extremely late in 2018, primarily due to the intrusion of easterly winds over the SCS. We show that the anomalous easterlies over the SCS associated with the delayed SCSSM could block the moisture transport from the tropical oceans to SC, which led to decreased rainfall, increased surface radiation, and elevated probability of heat wave in SC during May 2018. Further analysis reveals that both SC heat waves and SCSSM were significantly affected by the Pacific subtropical high (PSH). The westward extension of the PSH can hinder the establishment of SCSSM via inducing easterly anomalies over the SCS, which reduces SC rainfall and results in a drier surface condition. Moreover, the westward displacement of the PSH may cause anomalously high pressures, descending air motions, and divergent winds over SC, which triggers above-normal air temperatures that are conducive to the occurrences of SC heat waves. This study also underlines the importance of Eurasian planetary wave trains in bridging the upstream climate variability and the changes in PSH during boreal spring, which could be used to improve the intra-seasonal predictions of SC heat wave and SCSSM onset.

Traumatic Resin Duct Development, Terpenoid Formation, and Related Synthase Gene Expression in Pinus massoniana Under Feeding Pressure of Monochamus alternatus - Ruixu Chen; Xuanyu He; Juan Chen; Tianzi Gu; Pengcheng Liu; Tian Xu; Stephen A. Teale; Dejun Hao (Journal of Plant Growth Regulation, 2019)

Effects of exogenous methyl jasmonate-induced resistance in Populus × euramericana ‘Nanlin895’ on the performance and metabolic enzyme activities of Clostera anachoreta - Gu Tianzi; Zhang Congcong; Chen Changyu; Li hui; Huang kairu; Tian Shuo; Zhao Xudong; Hao Dejun (Arthropod-Plant Interactions, 2018)

Using eddy geopotential height to measure the western North Pacific subtropical high in a warming climate - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng; Bo Wu; Tianjun Zhou (Theoretical and Applied Climatology, 2018)

Interannual variability of Eastern China Summer Rainfall: the origins of the meridional triple and dipole modes - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2017)

Formation mechanism for the amplitude of interannual climate variability in subtropical northern hemisphere: relative contributions from the zonal asymmetric mean state and the interannual variability of SST - Chao He; Ailan Lin; Dejun Gu; Chunhui Li; Bin Zheng (Climate Dynamics, 2017)

How much of the interannual variability of East Asian summer rainfall is forced by SST? - Chao He; Bo Wu; Chunhui Li; Ailan Lin; Dejun Gu; Bin Zheng; Tianjun Zhou (Climate Dynamics, 2016)

Relationship between summer rainfall anomalies and sub-seasonal oscillations in South China - Chunhui Li; Tim Li; Ailan Lin; Dejun Gu; Bin Zheng (Climate Dynamics, 2015)

In vitro comparison of the hemocompatibility of diamond-like carbon and carbon nitride coatings with different atomic percentages of N - MengLi Zhao; DeJun Li; YiTeng Zhang; MeiXian Guo; XiangYun Deng; HanQing Gu; RongXin Wan (Science China Life Sciences, 2012)

Spatial patterns of Tropospheric Biennial Oscillation and its numerical simulation - Bin Zheng; Dejun Gu; Ailan Lin; Chunhui Li (Advances in Atmospheric Sciences, 2008)

Seasonal and interdecadal variations of heat transport over the northern hemisphere - Sun Jilin; Xu Delong; GU Dejun (Journal of Ocean University of China, 2006)